Near‐infrared spectroscopy monitoring in a pre‐hospital trauma patient cohort: An analysis of successful signal collection. Issue 1 (23rd July 2019) - Weatherall, Andrew; Poynter, Elwyn; Garner, Alan; Lee, Anna
Abstract : Background: Noninvasive monitoring of cerebral physiology could potentially guide pre‐hospital management of patients with traumatic injuries. Near‐infrared spectroscopy (NIRS) is one such modality but the consistency of monitoring performance remains unclear. This study assessed the proportion of successful signal collection during pre‐hospital care. Methods: As part of a prospective observational study, an independent study observer placed three sensors for a Nonin 7610 NIRS device; two on the forehead and one on the forearm. NIRS records were analysed for time of adequate monitoring signal in each sensor (>70% of total pre‐hospital time). We also compared pre‐hospital scene and transport times for patients with or without NIRS monitoring. Results: Sixty‐three patients with monitoring sensors applied were compared to 255 patients where no study observer was on board and 97 without NIRS monitoring for various reasons within the same time period. The proportion of pre‐hospital time with successful monitoring (>70%) was 71.4% (45 of 63) for all three sensors, with at least two sensors functional in 90.4% (57 of 63). The median (interquartile range) scene time was 19 (11‐23) minutes in patients with NIRS monitoring compared to 18 (11‐27) minutes without NIRS monitoring ( P = .570). There was no difference in the median (interquartile range) total pre‐hospital time between patients with or without monitoring sensors (72 [59‐89] versus 72 [59‐80] minutes; P = .605). Conclusions: In this pre‐hospital observational feasibility study with dedicated personnel an acceptable proportion of measurement time was achieved in over 90% of monitored subjects. Addition of NIRS monitoring did not alter pre‐hospital scene or transport times in this research setting.